Prevalence of fumonisin producing Fusarium verticillioides associated with cereals grown in Karnataka (India) - N. Deepa; H. Nagaraja; M.Y. Sreenivasa (Food Science and Human Wellness)
A total of 135 cereal samples were collected from different districts of Karnataka state, India in which 69 samples were infected with Fusarium species. Among these 51 samples were having Fusarium verticillioides infection and among them 42 samples were positive for fumonisin production. Per cent incidence and frequency were high in maize samples with 33.12% and 47.54%, respectively followed by paddy and sorghum, while pearl millet was free from F. verticillioides infection. Relative density of F. verticillioides association was 59.50% among the screened samples. A total of 326 Fusarium species were isolated by screening 135 cereal samples and among these 194 isolates of F. verticillioides scored positive for VERTF-1 and VERTR species-specific pair of primers. Further amplification with VERTF-1 and VERTF-2 pair of primers recorded 176 isolates of fumonisin producing F. verticillioides. The study revealed high incidence, frequency and relative density of fumonisin producing F. verticillioides and production of fumonisins in cereals. It was amplified using one forward and two reverse primers to discriminate fumonisin producing from fumonisin non-producing F. verticillioides which stresses the need for the development of managemental stratergies before they enter into the food chain.